2022
DOI: 10.3390/ijerph19073942
|View full text |Cite
|
Sign up to set email alerts
|

How Media Exposure, Media Trust, and Media Bias Perception Influence Public Evaluation of COVID-19 Pandemic in International Metropolises

Abstract: International metropolises are key sites of outbreaks of COVID-19 cases. Global public evaluation of the pandemic in international cities is affected by many factors. This study examines how media exposure affects this evaluation and how media trust and media bias perception moderate the relationship between them. Based on an online survey of the evaluation of 13 international cities’ pandemic performances by 1171 citizens from 11 countries, this study conducted a multi-level stepwise regression analysis and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…For self-media technology, before a new self-media work is released, it is necessary to evaluate whether the content of self-media technology will attract people's attention. For a professional self-media team, a self-media video will take a lot of time and financial and material resources, which requires this self-media content to attract more people's interest, which will achieve the expected effect, economic benefits [9,10]. e content of We Media is not only to spread the positive energy of the society but also use We Media to traditionally have more knowledge necessary for life.…”
Section: Introductionmentioning
confidence: 99%
“…For self-media technology, before a new self-media work is released, it is necessary to evaluate whether the content of self-media technology will attract people's attention. For a professional self-media team, a self-media video will take a lot of time and financial and material resources, which requires this self-media content to attract more people's interest, which will achieve the expected effect, economic benefits [9,10]. e content of We Media is not only to spread the positive energy of the society but also use We Media to traditionally have more knowledge necessary for life.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported repeated and higher media exposure to elevate COVID-19 related anxiety and stress [ 72 , 73 ]. Overtime, there has been dramatic changes in information diffusion, with internet technology making unprecedented amount of health information accessible to consumers, nonetheless, there are ambiguities associated with many information sources [ 74 , 75 ]. Thus, relying on fewer trusted information sources on COVID-19 could reduce psychological impact of the pandemics.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, it covers a wide spectrum of online platforms that allow user-generated content to be edited and shared in real-time through an interactive network, including social networking sites (SNS), blogs, microblogs, wikis, collaborative projects, forums, photo or video sharing sites, social bookmarking, social gaming and virtual realities (Aichner et al, 2021; Freberg & Kim, 2018). Regularly accessed by over 4.26 billion users worldwide (Statista, 2022), social media constantly feeds information and influences the minds of leaders, children, and anyone who uses it (Ferguson, 2021; Han et al, 2022; Melovic et al, 2020; Post & Ramirez, 2018; Tan & Jocz, 2017). Researchers, as science subject experts and social media users, can promote, educate and entertain non-expert laypeople about the benefits of science using social media.…”
Section: Introductionmentioning
confidence: 99%